Evolution and constitutional limits of the right to an effective remedy in the European Union - Agudo González, Jorge (2020)
The Court of Justice confirmed early that the principle of an effective remedy is a general principle of EU law. With the entry into force of the Lisbon Treaty and the EU Charter of Fundamental Rights, the foundation of case law turned to the Article 47 of the Charter, detecting progresses which suggest that the Court has assumed the task of conferring to said precept the effectiveness and the proper content that the protection of the rights recognized by EU law demands. In this paper we will expose the argumentative lines to which the Court has resorted to support the aforementioned fundamental right. Secondly, the common legal bases of these case law lines will be revealed, trying to show that there have not been qualitative differences that prevent to pose a unitary configuration of a same and unique right. Lastly, the intention is to define the content of this right with an integrative interpretation. This aim will show that the efficacy and content of the right have had an evolution that converges in similar fundamental parameters. Those parameters are materialized in levels of protection that, in general terms, are potentially more demanding than those derived from national constitutions.